BACKGROUND OF PREDICTION POLYMER PRICES THROUGH NEWS FLOW - Черенков, Игорь Александрович; Орехов, Сергей Валерьевич (Eastern-European Journal of Enterprise Technologies, 2010)
A price forecasting specific was described. Key indicators of price change were marked out. Problem definition and possible approaches for it solution were given.